Proposed Negative Statutory Instruments under the European Union (Withdrawal) Act 2018 : Draft International Accounting Standards and European Public Limited-Liability Company (Amendment etc.) (EU Exit) Regulations 2019 ; Draft Mobile Roaming (EU Exit) Regulations 2019 ; Draft Product Safety and Metrology etc. (Amendment etc.) (EU Exit) Regulations 2019 : 17th Report of Session 2017-19 /: Draft International Accounting Standards and European Public Limited-Liability Company (Amendment etc.) (EU Exit) Regulations 2019 ; Draft Mobile Roaming (EU Exit) Regulations 2019 ; Draft Product Safety and Metrology etc. (Amendment etc.) (EU Exit) Regulations 2019 : 17th Report of Session 2017-19. ([2019-02-21]) - Unknown
No abstract available